2020
DOI: 10.1016/j.ygyno.2020.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Electronic patient-reported symptom monitoring in patients recovering from ambulatory minimally invasive gynecologic surgery: A prospective pilot study

Abstract: Objective To evaluate the feasibility of an electronic symptom-tracking platform for patients recovering from ambulatory surgery. Method We assessed user response to an electronic system designed to self-report symptoms. Endpoints included compliance, postoperative symptoms, patient satisfaction. An 8-item symptom inventory (pain, nausea, vomiting, shortness of breath, fever, swelling, discharge, redness) was developed and made available on postoperative days (POD) 2–6.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 23 publications
0
26
0
1
Order By: Relevance
“…Most patient-reported problems after minimally invasive gynecologic surgery include pain, vaginal bleeding, urinary tract infection and surgical site infection [ 26 28 ]. This study showed that the most common postsurgical problems of minimally invasive gynecologic surgery were vaginal bleeding, followed by mild pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most patient-reported problems after minimally invasive gynecologic surgery include pain, vaginal bleeding, urinary tract infection and surgical site infection [ 26 28 ]. This study showed that the most common postsurgical problems of minimally invasive gynecologic surgery were vaginal bleeding, followed by mild pain.…”
Section: Discussionmentioning
confidence: 99%
“…To verify the correlations between the three variables, three telephone interviews were conducted with patients to investigate these postsurgical outcomes. Most patient-reported problems after day gynecologic surgery include constipation, diarrhea, pain, vaginal bleeding, urinary tract infection and surgical site infection [ 26 28 ]. In this study, we included these problems on our postsurgical outcomes form.…”
Section: Introductionmentioning
confidence: 99%
“…Manfaat lainnya pada pasien kanker ginekologi yaitu sangat layak dalam melacak pasien yang telah melakukan operasi ginekologi (Hay et al, 2016). Dengan adanya pelaporan gejala secara langsung tanpa adanya perspektif dari oranglain, gejala psikologis ikut menjadi perhatian sejalan dengan mengatasi gejala fisik (Zivanovic et al, 2020). Tinjauan pustaka ini mungkin saja menjadi yang pertama dalam mengeksloprasi manajemen gejala kanker jarak jauh pada pasien kanker ginekologi.…”
Section: Hasil Dan Pembahasanunclassified
“…The current lack of theoretically based interventions to teach self-advocacy skills [ 10 , 11 ] prevents patients with low self-advocacy skills from effectively engaging in their care and puts them at risk for poor outcomes such as poor symptom management, low quality of life, and lack of patient-centered care [ 13 , 14 ]. This is particularly true for individuals who are newly diagnosed with cancer when treatment decisions are often complex, cancer- and treatment-related symptoms and have a huge impact on quality of life and managing social support can be challenging.…”
Section: Introductionmentioning
confidence: 99%